Navigating the Indonesian-Philippine Border: The Challenges of Life in the Borderzone - Velasco, Djorina (Kasarinlan: Philippine Journal of Third World Studies; Vol 25 No 1-2 (2010): Political Economy of Ideas, 2010)
The paper explores border issues on the Indonesian side of the Indonesian-Philippine border by surfacing the contestations between state and society over the maintenance of the border and the social construction of identities and space, in particular the maritime border that connects the two countries. This interplay between identity, borders, and statehood places into context the long history of “illegal” border crossing in the Sulawesi-Sulu Sea that continues to the present. The paper puts forward a critique of the security and cultural approaches on border issues for not being sufficiently attuned to realities on the ground and demonstrates that the needs of border populations are better served by a more inclusive and consultative approach to understanding the particularities of their situation.
Keywords: border studies; maritime borders; governmentality; Sulawesi-Sulu sea